Pendampingan Implementasi Kurikulum Merdeka Belajar Bagi Guru MGMP Jatirogo Tuban Selatan - Damayanti, Rini; kaswadi, kaswadi; pranoto, agung; Ardiansyah, Roely; hadi, sueb; Davin, Moch Arya (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
The Merdeka Curriculum will be implemented simultaneously at the secondary education level in 2024. Even at the junior high school level, especially grade VII, in the 2023/2024 school year, the Merdeka Curriculum has been implemented. The implementation of the Merdeka Curriculum requires teachers' understanding and readiness of the Merdeka Curriculum with its various components and applications. Realistic conditions in the field show that junior high school teachers do not fully understand the Merdeka Curriculum, especially regarding Learning Outcomes, Learning Objectives, Learning Objective Flow, and Teaching Modules and their modifications. The purpose of the service activity is to increase teachers' knowledge, understanding of the Merdeka Curriculum and produce learning tools. The method used in this service is training assistance in the form of a workshop. The results of the activity show that the teachers have understood the concept of the Merdeka Curriculum, especially Learning Outcomes, Learning Objectives, Learning Objective Flow, and Teaching Modules and their applications. This can be seen from the work of the teachers in embodying these concepts in the flow of learning objectives and teaching modules as lesson plans to be implemented. In other words, junior high school teachers in the South Tuban Indonesian Language MGMP are not ready to implement the Merdeka Curriculum.ABSTRAKKurikulum Merdeka akan dilaksanakan secara serentak di jenjang pendidikan menengah pada tahun 2024. Bahkan di tingkat SMP, khusus kelas VII, pada tahun ajaran 2023/2024 Kurikulum Merdeka sudah diberlakukan. Implementasi Kurikulum Merdeka memerlukan pemahaman dan kesiapan guru tentang Kurikulum Merdeka dengan berbagai komponen dan aplikasinya. Kondisi realistis di lapangan menunjukkan bahwa guru SMP belum memahami secara utuh tentang Kurikulum Merdeka, khususnya tentang Capaian Pembelajaran, Tujuan Pembelajaran, Alur Tujuan Pembelajaran, dan Modul Ajar serta modifikasinya. Tujuan kegiatan pengabdian adalah untuk meningkatkan pengetahuan, pemahaman para guru tentang Kurikulum Merdeka dan menghasilkan perangkat pembelajaran. Metode  yang  digunakan  dalam  pengabdian  ini  adalah pendampingan pelatihan dalam bentuk workshop. Hasil kegiatan menunjukkan bahwa para guru telah memahami konsep Kurikulum Merdeka, khususnya Capaian Pembelajaran, Tujuan Pembelajaran, Alur Tujuan Pembelajaran, dan Modul Ajar serta aplikasinya. Hal tersebut dapat dilihat dari hasil kerja para guru dalam mengejawantahkan konsep tersebut dalam Alur Tujuan pembelajaran dan Modul Ajar sebagai rencana pembelajaran yang akan dilaksanakan. Dengan kata lain, para guru SMP di MGMP Bahasa Indonesia Tuban Selatan belum siap mengimplementasikan Kurikulum Merdeka.